From Factory Floor to Market the Role of Just-in-Time and Lean Operations in Enhancing Competitive Advantage - Sudjaniah, Derah; Nasrullah; Jailani; Dharmawan, Handhika; Miko, Nanda Temas (International Journal of Social Service and Research, 2025)
This study aims to analyze the influence of lean practices and just-in-time (JIT) practices on the competitive advantage of Indonesian manufacturing companies, with time-to-market speed as a mediating variable. A quantitative approach was employed using data from 150–200 respondents and analyzed using Structural Equation Modeling (SEM) via AMOS. The results show that lean practices significantly influence competitive advantage and accelerate time-to-market. Time-to-market speed serves as a significant mediator between lean and competitive advantage. Conversely, while JIT has a direct positive effect on competitive advantage, its impact on time-to-market is insignificant. This study is limited by its sample size and geographic focus, which may affect the generalizability of the findings to other regions or industries outside the Indonesian manufacturing sector. These findings highlight the importance of strengthening lean practices in the Indonesian manufacturing context and emphasize the need for system readiness to implement JIT effectively. This study contributes to the existing literature by examining time-to-market as a mediating variable and by providing empirical insights into how lean and JIT practices influence competitive advantage in an emerging market context.